BAURAN PEMASARAN JASA (3 Ps : PEOPLE, PROCESS & PHYSICAL EVIDENCE) BAGI KEPUASAN PELANGGAN - Muhammad Wadud (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study discusses how the performance of loading and unloading companies that provide services to customers. The purpose of this study is to know how the involvement of employees, work processes and physical environment in providing services loading and unloading ports so as to provide customer satisfaction. Research location at PT. Gajah Unggul Internasional located in Boom Baru Palembang, the data used combination of primary data and secondary data with the number of respondents as many as 100 company. Data collection techniques through observation and questionnaires. The variables of this study are endogenous and exogenous variables. Endogenous variables consist of people, process and physical evidence. While the exogenous variable is customer satisfaction. To measure the effect of variables using the SEM method with the amos version 22 program that was processed based on a simple linear regression model. From the results of the research data obtained information that the variables of people, process and physical evidence give influence to customer satisfaction, but from the three variables studied only process variables that give a negative effect on customer satisfaction, this is caused by the complexity of administrative matters so that service less satisfactory and do not give satisfaction to customers. The limitations of this study only focus on aspects of people, processes, and the physical environment, because there needs to be other aspects that need to be researched so that the information obtained more konfrehensif.Keywords :Participant (People), Process, Physical evidence, Marketing mix Services